Productivity enhancement in animal production systems in Asia - Devendra, C. (Society for the Advancement of Breeding Researches in Asia and Oceania, 2001)
The justification for productivity enhancement in animal production systems in Asia is discussed in the context of major economic changes and a changing external environment, and the inability of current systems of animal production to meet the human requirements of foods of animal origin. The situation is exacerbated by such factors as rapid population growth, urbanization, increased incomes, demand-led processes and changing consumer preferences. The projected total meat and milk requirement levels in 2020 are far in excess of anticipated supplies, and place unprecendented pressure on improved and integrated management of the natural resources (crops, animals, land and water). Enhancing productivity is therefore compelling, and will need to come from improved efficiency in the management of natural resources, increased per animal performance, appropriate animal production systems, and higher efficiency in the use of feed resources. Presently, the intensive, industrialized and private sector-led non-ruminant sector supplies the bulk of the meat and eggs for human consumption. By comparison, ruminant production systems have lagged behind in productivity because of inadequate technology application and participation of resource poor small farmers. Since arable land is limited and existing irrigated land are overused, the potentially important rainfed lands will become increasingly important to productivity enhancement in the future. Increased research investments are necessary that can specifically focus on these environments, backed by strong systems research approach, interdisciplinary and holistic approach. These together can significantly benefit both producers and consumers, promote improved livelihoods for the poorest of the poor, agricultural growth and environmental sustainability.